CRP and SAA1 Haplotypes Are Associated with Both C-Reactive Protein and Serum Amyloid A Levels: Role of Suppression Effects - Yu-Lin Ko; Lung-An Hsu; Semon Wu; Ming-Sheng Teng; Hsin-Hua Chou (Mediators of Inflammation)
To test the statistical association of the CRP and SAA1 locus variants with their corresponding circulating levels and metabolic and inflammatory biomarker levels by using mediation analysis, a sample population of 599 Taiwanese subjects was enrolled and five CRP and four SAA1 variants were genotyped. Correlation analysis revealed that C-reactive protein (CRP) and serum amyloid A (SAA) levels were significantly associated with multiple metabolic phenotypes and inflammatory marker levels. Our data further revealed a significant association of CRP and SAA1 variants with both CRP and SAA levels. Mediation analysis revealed that SAA levels suppressed the association between SAA1 genotypes/haplotypes and CRP levels and that CRP levels suppressed the association between CRP haplotypes and SAA levels. In conclusion, genetic variants at the CRP and SAA1 loci independently affect both CRP and SAA levels, and their respective circulating levels act as suppressors. These results provided further evidence of the role of the suppression effect in biological science and may partially explain the missing heritability in genetic association studies.